Risk assessment of aflatoxins and selected heavy metals through intake of branded and non-branded spices collected from the markets of Multan city of Pakistan. (June 2020) - Akhtar, Saeed; Riaz, Muhammad; Naeem, Iqra; Gong, Yun Yun; Ismail, Amir; Hussain, Majid; Akram, Kashif
Abstract: Spices are an essential part of our food preparations and are considered a potential source of health-protective components. However, spices may also contain some toxic substances primarily aflatoxins and heavy metals. This study aimed to quantify the level of total aflatoxins and three most toxic heavy metals i.e. lead (Pb), arsenic (As) and cadmium (Cd) in commercially available non-branded and branded spices. Furthermore, risk assessment through aflatoxins and heavy metals was performed by computing the values of Margin of Exposure (MOE) and Total Hazard Quotient (THQ), respectively. The concentration of aflatoxins was recorded higher in non-branded spices while heavy metals especially Pb was recorded higher in branded spices. MOE values for aflatoxins through spices consumption indicated that all age group of people were consuming aflatoxins above the threshold level. The THQ values for heavy metals toxicity assessment were found within the acceptable ranges. Females, especially above 24 years of age, were found at more risk as compared to male, due to their higher intake rate of spices. Highlights: Aflatoxins and heavy metals were quantified in branded and non-branded spices. Branded spices were found less contaminated as compared to non-branded. Margin of Exposure values indicated the chances of toxicity in all age groups. Total Hazard Quotient values for heavy metals were found within safe ranges.